Role and Cultural Persistence of Tominaa in Toraja Funeral Traditions - Sakmawati, Sakmawati; Shasliani, Shasliani (Program Studi Tadris IPS Institut Agama Islam Negeri (IAIN) Parepare, 2025)
Background: Research on the dynamics of Toraja death rituals has generally emphasized visual aspects such as Tongkonan architecture, the slaughter of sacrificial animals, or mass processions. However, the role of the Tominaa as guardians and preservers of ritual traditions has not been sufficiently explored.Purpose: This study aims to investigate the presence of Tominaa in the funeral traditions of the Toraja people, which have changed over time. As indigenous oral poets, Tominaa lead ceremonies by chanting sacred verses known as kadong badong or tumba and serve as crucial pillars in preserving the cosmology and values of Aluk Todolo, the ancestral faith.Method: The research employs a literature review approach, analyzing previous scholarly works, theoretical frameworks, and key findings related to the role of Tominaa in Toraja funeral traditions.Results: The findings indicate that the role of Tominaa extends beyond ceremonial leadership, encompassing cultural guardianship, the preservation of identity, and the safeguarding of Toraja spirituality.Theoretical implications: This study enriches the understanding of Toraja culture and provides a living laboratory for abstract Social Studies concepts, thereby deepening comprehension of Indonesia’s sociocultural dynamics.Practical implications: Recognizing the Tominaa as custodians of ritual knowledge underscores the need for cultural preservation efforts through intergenerational transmission, integration into local education, and supportive policies, ensuring the continuity of Toraja’s intangible heritage amidst modernization.